International Journal of Intelligent Robotics and Applications - Yin, Zhouping; Lee, Kok-Meng.; Liu, Honghai; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
The International Journal of Intelligent Robotics and Applications (IJIRA) fosters the dissemination of new discoveries and novel technologies that advance developments in robotics and their broad applications. This journal provides a publication and communication platform for all robotics topics, from the theoretical fundamentals and technological advances to various applications including manufacturing, space vehicles, biomedical systems and automobiles, data-storage devices, healthcare systems, home appliances, and intelligent highways. IJIRA welcomes contributions from researchers, professionals and industrial practitioners. It publishes original, high-quality and previously unpublished research papers, brief reports, and critical reviews. Specific areas of interest include, but are not limited to: Advanced actuators and sensors Collective and social robots Computing, communication and control Design, modeling and prototyping Human and robot interaction Machine learning and intelligence Mobile robots and intelligent autonomous systems Multi-sensor fusion and perception Planning, navigation and localization Robot intelligence, learning and linguistics Robotic vision, recognition and reconstruction Bio-mechatronics and robotics Cloud and Swarm robotics Cognitive and neuro robotics Exploration and security robotics Healthcare, medical and assistive robotics Robotics for intelligent manufacturing Service, social and entertainment robotics Space and underwater robots Novel and emerging applications.
Keywords: User interfaces (Computer systems).; Control engineering; Robotics; Mechatronics; Electronics; Microelectronics; Artificial Intelligence; Control, Robotics, Mechatronics; User Interfaces and Human Computer Interaction; Manufacturing, Machines, Tools, Processes; Electronics and Microelectronics, Instrumentation